STRATEGI PENGEMBANGAN AGRIBISNIS PADI ORGANIK PADA KOMUNITAS PETANI ORGANIK ASTORAHAYU DESA ASTOMULYO, KECAMATAN PUNGGUR, LAMPUNG TENGAH - Aan Andika; Khairul Amri; Zulkarnaen Zulkarnaen (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2022)
Public demand for rice food has increased while the availability of organic rice is still limited. So that organic rice farming is more promising to be developed. This study aims to determine the agribusiness developing strategy for organic rice in the Astorahayu Organic Farmers Community, Astomulyo Village, Punggur District, Central Lampung Regency. The analytical methods used are IFE, EFE, IE, Analysis of Strengths, Weaknesses, Opportunities, Threats (SWOT), and Analytical Hierarchy Process (AHP). The analysis results showed that the IFE matrix's weight is 2.70, and the EFE matrix is 2.35. The IE matrix is in a hold and maintains position with a market penetration strategy and product development. SWOT analysis produces 12 alternative strategies that can be applied for organic rice expansion. The AHP results show that the level of criteria are the main priority in developing organic rice are increasing marketing and institutionalization with a weight of 0.301. At the objective level, the primary importance of developing the organic rice agribusiness system is expanding the production capacity of organic rice with a weight of 0.508. At the actor level, the farmer in the Astorahayu organic paddy community with a weight of 0.435. The primary priority alternative strategy is to improve the skills of organic rice cultivation by utilizing the cooperation of the organic farming community members to increase productivity with a weight of 0.183.